Pengaruh Kompetensi Wirausaha dan Pendidikan terhadap Produktivitas Pelaku Ekonomi Kreatif Kota Pangkalpinang dimediasi oleh Motivasi Wirausaha - Musa, Jacqueline Aprilia; Wibawa, Dian Prihardini; Saputra, Darman (Benefit: Jurnal Manajemen dan Bisnis, 2024)
This study aims to reveal the effect of entrepreneurial competence and education on productivity in creative economic actors in Pangkalpinang City, with entrepreneurial motivation as an intervening variable. The research method used is descriptive quantitative with data collection involving 90 respondents of creative economy business actors in Pangkalpinang City with purposive sampling through distributing questionnaires. This research uses a Structural Equation Model (SEM) with SMARTPLS software. The results of this study indicate that entrepreneurial competence and entrepreneurial motivation have a positive and significant effect on productivity partially. In contrast, education has a negative and significant effect on productivity. In addition, the indirect test results show that entrepreneurial competence and education have a positive and significant effect on productivity when it is mediated by entrepreneurial motivation. Keywords: Entrepreneurial Competence, Education, Productivity, Entrepreneurial Motivation